The Effectiveness of Vitamin C Addition to Blood Glucose Levels of Hyperglycemic Mice with Glimepiride Treatment - Indi Kamilia Fitri; Cholis Abrori; Dion Krismashogi Dharmawan (Journal of Agromedicine and Medical Sciences, 2020)
In people with diabetes mellitus (DM) there is a decrease in basal vitamin C levels which is thought to be a result of oxidative stress in the condition of hyperglycemia that it needs to increase vitamin C as an antioxidant. Hyperglycemia in DM needs to be lowered by pharmacological therapy, named glimepirid so the purpose of this study is to determine the effectiveness of vitamin C addition to the reduction of KGD hyperglycemic mice with glimepirid treatment. This study is true experimental with a sample of 25 mice 20-30 grams and divided into five groups, first the control group (K0); STZ induction group (K1); STZ induction group with glimepirid treatment (K2); STZ induction group with the treatment of vitamin C (K3); STZ induction group by treatment of a combination of glimepirid and vitamin C (K4). STZ is injected intraperitonially 150 mg / kgBB. All groups were measured for KGD 1 after induction of STZ and KGD 2 after treatment for fourteen days. The results of the STZ induction group with the treatment of a combination of glimepirid and vitamin C (K4) experienced a smaller and not significant decrease in BSL in the STZ induction group with a single glimepirid (K2) treatment. These results are thought to have an influence from interactions between drugs that cause one drug to not work optimally. The conclusion of this study is that administration of glimepirid, vitamin C, or both can reduce blood glucose levels in hyperglycemic mice with the greatest decrease occurring in the glimepirid group.